SAGE qualitative research methods - Atkinson, Paul, 1947-; Delamont, Sara, 1947- (Sage benchmarks in social research methods., 2010)
SAGE has been a major force shaping the field of qualitative methods. This collection includes research from the past four decades and addresses key issues or controversies, such as explanations and defences of qualitative methods, ethics research questions and foreshadowed problems, access, and first days in the field.